Production and wear properties of metal matrix composites reinforced with boride particles - Savas, Omer; Kayikci, Ramazan (ELSEVIER SCI LTD, 2013)
Production and properties of metal matrix composites reinforced with in situ cuboidal boride particles have been investigated. Boron 3 weight (wt.)% was dissolved in an aluminium copper alloy at 1400 degrees C through direct addition of boron oxide (B2O3) which resulted in 6.14 volume (vol.)% reinforcing phase of cuboidal boride particles in the alloy. Higher reinforcement volume per cent of in situ boride particles in the Al-Cu matrix has been produced by using a filtration device. Metallographic examinations, optical microscopy, and a wet chemistry analysis technique for determination of boron content have been used to reveal the structure and the volume fraction of the reinforcement phase. The wear behaviour of the composite and matrix were investigated using a pin-on-disk tester under different conditions. Results showed that average cumulative weight loss of the new composite can be decreased by 68% with addition of 33 vol.% of cuboidal boride particles into the Al-Cu matrix. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: MECHANICAL-PROPERTIES; SITU; ALB2; MICROSTRUCTURE; Materials Science